2007
DOI: 10.1038/sj.gt.3302893
|View full text |Cite
|
Sign up to set email alerts
|

Mannan-modified adenovirus as a vaccine to induce antitumor immunity

Abstract: Tumor vaccine is a useful strategy for cancer therapy. However, priming of the immune system requires the relevant antigen to be presented by antigen-presenting cells (APCs). Here, we employed telomerase reverse transcriptase as a model antigen to explore the feasibility of using mannan-modified adenovirus as a tumor vaccine. We found that tumor immunogene therapy with the vaccine was effective at protective antitumor immunity in mice. The antigen-specific cytotoxic T lymphocytes were found in in vitro cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…3). Compared with previous single antigen-encoding strategies developed in our laboratory28, the combination virus was more effective for stimulation of DCs and provided a more potent anti-tumour immune response that significantly improved survival.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…3). Compared with previous single antigen-encoding strategies developed in our laboratory28, the combination virus was more effective for stimulation of DCs and provided a more potent anti-tumour immune response that significantly improved survival.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that mannan modification significantly enhances antigen identification and uptake by splenic DCs28, or the lymph nodes DCs29, and leads to the activation of specific T lymphocytes. It was shown that spleen DCs could process and present antigens efficiently irrespective of the route of antigen capture30, therefore we take the convenience to manipulate and more intuitive method (spleen sections) to investigate the antigens delivering into DCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…173 Mice immunized by intraperitoneal injection were apparently protected from tumor growth and the survival of the tumor-bearing mice treated with AdT-m was also longer than that of the control group. In another study, mice were immunized with DEC-205 targeted DNA vaccines and boosted with adenoviral vectors encoding OVA and HIV Gantigen-p41 as antigens.…”
Section: In Vitro and In Vivomentioning
confidence: 94%
“…These delivery systems are promising tools for cancer therapy, but serious concerns arise from their immunogenicity and instability in blood circulation. 165 Viruses, such as HVJ (hemagglutinating virus of Japan; Sendai virus), [166][167][168] influenza virus, 50 169 170 and adenovirus, [171][172][173] have been used in the construction of virosomes.…”
Section: In Vitro and In Vivomentioning
confidence: 99%